2001
DOI: 10.1063/1.1372356
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of second-harmonic generation in a one-dimensional semiconductor photonic band gap

Abstract: We demonstrate significant enhancement of second-order nonlinear interactions in a one-dimensional semiconductor Bragg mirror operating as a photonic band gap structure. The enhancement comes from a simultaneous availability of a high density of states, thanks to high field localization, and the improvement of effective coherent length near the photonic band edge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(75 citation statements)
references
References 11 publications
0
75
0
Order By: Relevance
“…We note that an increase of electric-field amplitudes in the area of periodic corrugation is small compared with that occurring in layered photonic band-gap structures (with a deep grating) [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…We note that an increase of electric-field amplitudes in the area of periodic corrugation is small compared with that occurring in layered photonic band-gap structures (with a deep grating) [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that intense nonlinear processes can occur in such structures built up from nonlinear materials. For example, second harmonic and sub-harmonic generation has been predicted and also observed [3,4]. Advantages of these structures from the point of view of nonlinear interactions are based on high densities of local optical modes, on spatial localization of optical modes in confined regions of the structure and in convenient fulfilling of phase-matching conditions of a given nonlinear process.…”
Section: Introductionmentioning
confidence: 99%
“…Evolution of the nonlinearly-interacting quantum optical fields inside the waveguide is described by the following momentum operatorĜ [9,23]: [56][57][58][59]. On the other hand, the nonlinear coupling constants K nl,q (ω s , ω ′ s ) characterize the nonlinear interaction among co-propagating fields and obey the symme-…”
Section: Quantum Multi-mode Model Of Second-subharmonic Generationmentioning
confidence: 99%